PENGARUH MODEL PEMBELAJARAN SAVI (SOMATIC, AUDITORY, VISUAL, INTELLECTUAL) TERHADAP HASIL BELAJAR IPA SISWA KELAS VIII SMP SWASTA YPI DHARMA BUDI KECAMATAN SIDAMANIK - Dianti Siboro, Thiur; Mustika Piliang, Fenny; Ariska, Windy (Jurnal Metabio, 2024)
This research aims to determine the effect of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model on the science learning outcomes of class VIII students at YPI Dharma Budi Private Middle School, Sidamanik District, Academic Year 2023/2024. The population in this study were all class VIII students consisting of 2 classes with a total of 60 students. Sampling was carried out using non-probability sampling, saturated sampling or total sampling. Data analysis was carried out by determining the validity test, reliability test, linearity test, normality test, homogeneity test, R2 test, and hypothesis test, proven by the "t test" at a significance level of α = 0.05. From the research results, the average pretest score for the experimental class was 51.17 and the control class was 48.50. The average posttest score for the experimental class was 84.67 while the control class was 80.33 with a difference of 4.34. From the results of hypothesis testing using the t test, tcount (2.244) ˃ ttable (2.001), then Ha is accepted and H0 is rejected, meaning that there is an influence of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model on the science learning outcomes of class VIII students at YPI Dharma Private Middle School. Budi, Sidamanik District. And the results of this research show that the influence of the SAVI learning model on the science learning outcomes of class VIII students at Sw YPI Dharma Budi Sidamanik Middle School is 64.2%. Based on the results of research and data analysis, it can be concluded that there is an influence of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model on the science learning outcomes of class VIII students at YPI Dharma Budi Private Middle School, Sidamanik District, amounting to 64.2%.